Place-based education as a framework for tourism education in secondary schools: A case study from the Okavango Delta in Southern Africa. (November 2019) - Velempini, Kgosietsile; Martin, Bruce
Abstract: Tourism has been identified as a potential source of economic development and diversification in many developing countries. However, many of these countries are unable to fully leverage this potential due to a lack of human resource capacity within the hospitality and tourism industry. This lack of capacity is due in part to inadequate educational programming in the area of hospitality and tourism at secondary and tertiary levels. This study sought to address this problem through an exploration of the extent to which tourism education is incorporated into the secondary school curriculum in Botswana as well as ways to more fully do so. In particular, the researchers considered the potential value of place-based education as a theoretical framework for more fully incorporating tourism education into the secondary school curriculum in Botswana. The researchers relied on findings from a case study of a secondary school located in the Okavango Delta of Botswana to accomplish these two aims. The researchers found that tourism is addressed only to a limited extent within the school curriculum and that clear opportunities exist to enhance tourism education in secondary schools in Botswana.